Approaches to deposit pricing: a study in the determination of deposit interest and bank service charges - Juha Tarkka (Bank of Finland, 1995)
Table of Contents: 1 Introduction 11 2 Price parameters of the deposit relationship 15 2.1 Dimensions of pricing 15 2.2 The tariff function 18 3 On the historical development of demand deposit pricing 22 3.1 The classical period of deposit pricing 22 3.2 The period of regulated banking 26 3.3 The new competition 30 4 Theories of deposit account pricing 35 4.1 The free competition model 35 4.2 The monopolistic approach 36 4.3 The implicit interest question 39 4.4 The multiproduct approach 43 5 Developing the theory of deposit pricing 45 5.1 Essay I: The risk sharing explanation 46 5.2 Essay II: The tax explanation 48 5.3 Essay III: The price discrimination explanation 49 5.4 Essay IV: Switching costs 51 6 Conclusions 52 References 54 Appendix The deposit account terms offered by a Finnish bank in 1995 59
URN:NBN:fi:bof-201408071674
Keywords: 330